The Influence of the Development Trends of the Globalization Process on the Activity of the World Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The economic situation of international relations is determined by globalization processes. Although the single definition and consequences of this phenomenon cannot be accurately assessed, the prevailing idea is that economic, political and cultural processes spread between states and, on this basis, form a new unity of the world space. Globalization in modern conditions is determined by several factors: - the processes of inter-period integration of economic life, that is, the influence of capital, free movement of goods and interaction of national economies. The main participants of this process are multinational companies, international banks and other financial organizations.